Institutional corruption in the criminal justice system: The case of Ferguson - Wakeham, Joshua (Crime, law and social change, 2023)
This article argues that criminal justice scholars should import the theory of institutional corruption from political science to make sense of a distinct set of problems in the criminal justice system. To make this argument, this article examines the case of Ferguson, Missouri. In Ferguson, the city’s mandate to maximize revenue generation had a corrosive effect on the day-to-day policies and practices of both the Ferguson Police Department and the municipal court, leading to aggressive policing, excessive fines, and a number of unfair and unconstitutional practices. Framed as a problem of institutional corruption, the case of Ferguson is emblematic of a broader set of issues in criminal justice institutions involving policies and practices that are legal but rife with corrupting incentives. Such problems demand further scrutiny from criminal justice scholars and practitioners alike.